Ancient Technologies in Contexts of the Sustainable Development Goals - Kirsten Dzwiza (EXARC Journal)
The demand for innovative solutions to pressing ecological and societal challenges is on a constant rise. Ancient technologies provide extensive yet underutilized opportunities to help solve such problems. This paper presents three of these technologies and their successful application in modern contexts based on five illustrating case studies: Clay pot irrigation, Dhajji dewari, and the shinbashira. Clay pot irrigation is an auto-regulative irrigation method especially useful in sustainable small-scale farming, horticulture, vegetable gardening, and afforestation in arid and semi-arid regions. Dhajji dewari and the shinbashira are two earthquake-resistant construction technologies from Kashmir and Japan. Today, dhajji dewari is mainly used for private housing, while the shinbashira is applied in large buildings. Clay pot irrigation is simple, comparably cheap, and it is easy to get involved in experimental research and application as an individual. The two earthquake-resistant construction technologies, on the other hand, require more resources concerning time and funding, as well as a team. The objective of this paper is to raise awareness for the positive impact of ancient technologies on local, regional and national levels in contexts of climate change adaptation, disaster management, and in earthquake prone areas. It also aims to inspire more archaeologists to become involved in this area of research.